Recovery of Flow-Mediated Vasodilatation after Repetitive Measurements Is Involved in Early Vascular Impairment: Comparison with Indices of Vascular Tone - Inaba, Hatsumi (Public Library of Science, 2014)
In repetitive measurements of flow-mediated dilatation (FMD), the duration of the interval between measurements remains controversial. In this pilot study, we conducted three sequential measurements of low–flow-mediated constriction (L-FMC), FMD and flow-mediated total dilation (FMTD; L-FMC+ FMD) at baseline and intervals of 15 and 60 min in 30 healthy males. FMD(15), L-FMC(15), and FMTD(15) were significantly lower than the respective first measurements, but all indices showed full recovery at 60 min in all subjects. The baseline diameter was slightly increased at 15 min and restored at 60 min, but the maximum diameter, and the baseline and reactive flow velocity unchanged. We examined the relationship between recovery rate of FMTD at 15 min (FMTD-R) and cardio-ankle vascular index (CAVI). Univariate analysis showed moderate correlation between FMTD-R, and CAVI and L-FMC(0). Patients were divided according to FMTD-R value; the low-FMTD-R group [below the median value (−26.2%)] included a significantly higher proportion of smokers and higher CAVI values than the high-FMTD-R group. The reproducibility of FMTD and FMTD-R was evaluated in another group of 25 healthy subjects. The range of variation across measurements was 1.1% for FMTD and 4.6% for FMTD-R; with intraclass correlation coefficients of 0.93 and 0.95, respectively. The present study demonstrated blunted recovery of FMD within 15 min, suggesting the need for selection of a more adequate interval between measurements to avoid underestimation of FMD in subsequent measurements. The findings demonstrated the reproducibility of FMTD-R and FMTD measurements, and that FMTD-R might be involved in arterial stiffness and early vascular impairment in the healthy subjects.